2018
DOI: 10.1016/j.appet.2018.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Wasted food: A qualitative study of U.S. young adults' perceptions, beliefs and behaviors

Abstract: U.S. consumers, namely young adults, are one of the largest sources of preventable food waste. However, the antecedents of wasted food among young adults in the U.S. are unknown. This study aimed to explore the perceptions, beliefs and behaviors related to wasted food among 18- to 24-year-old adults. Fifty-eight individuals (63.8% female) with an average age of 20.2 y (±1.6) who lived in a residence where they had control over some food purchases (excluding co-op or other communal housing, and living with pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 30 publications
4
76
0
Order By: Relevance
“…We recognise that the behaviours of individuals can also be possible factors that strengthen (or break) food-related norms in a household or in a community ( Nikolaus, Nickols-Richardson, & Ellison, 2018 ; Parizeau et al, 2015 ). This potential dynamic is represented by the arrow in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We recognise that the behaviours of individuals can also be possible factors that strengthen (or break) food-related norms in a household or in a community ( Nikolaus, Nickols-Richardson, & Ellison, 2018 ; Parizeau et al, 2015 ). This potential dynamic is represented by the arrow in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some consumers feel guilty when they or other people waste food, so they will reduce food waste. The remaining consumers think that food waste has no direct impact on others and choose to ignore it [48,90]. Therefore, the more positive the attitude towards behavior is, the more consumers have the tendency of planning shopping and not wasting food, and the more likely such consumers are to become supervisors to prevent others from wasting food.…”
Section: Discussionmentioning
confidence: 99%
“…Young people spend less time on cooking and prefer fast food, while older people have more cooking skills and more time to engage in cooking activities [47]. As young people often buy fast food, seldom cook food, and have no idea about food materials, they generally have a low awareness of food waste and mistakenly believe that they have not caused much waste [48]. Therefore, it is necessary to guide emerging adult people to establish correct consumption concepts and values in order to reduce food waste behaviors and phenomena.…”
Section: Emerging Adulthood and Food Waste Behaviormentioning
confidence: 99%
“…Over time, it has been observed that there are cases in which the consumers are buying more food than needed and are storing it incorrectly [15]. Mattar et al [16] believe that employment, education, number of household members, and income may affect food waste volume, while Nikolaus et al [17] analyzed the believes and behavior of young adults in relation with the food waste and concluded that this category provides evidence of heterogeneity in perceptions, believes and behaviors. Also, Corrado et al [18] have shown that one third of the food produced globally is wasted along the food chain, while a series of studies made over different countries in the European Union, such as Italy, Germany, or Switzerland [19][20][21][22], have indicate that the households are the main contributors to food waste [19].…”
Section: Literature Reviewmentioning
confidence: 99%